Utilization of Biomass in Sustainable Integrated Dairy and Coffee Farming: CaseStudy Boyolali, Central Java, Indonesia - Hutahaean, Lintje; Rustiadi, Ernan; Fauzi, Anas Miftah; Nurmalina, Rita; Rubiyo (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
The agricultural sector plays a strategic role in improving economic sustainability and responding to environmental challenges. A sustainable agricultural approach based on the integration of coffee and dairy cattle is a potential solution to these challenges. This study aims to analyze financial feasibility by comparing two types of coffee and dairy cattle integration farming systems, namelytype 1 (existing coffee-dairy cattle integration) and type 2 (improved integration). The difference between the two types lies in the connectivity of input and output use in the integration system. The method used is financial feasibility analysis with investment criteria indicators in the form of NPV, IRR, Net B/C, and payback period. The research was conducted in Boyolali Regency. The resultsof the financial feasibility analysis show that the improved coffee and dairy cow integration type (type 2) is financially superior to type 1, with an NPV of IDR 1,714,402,922.83 and an IRR of 22%, far exceeding type 1 (IRR of 16%), with a payback period of 6 years and 8 months. This financial benefit came from lower costs for feed, energy, and fertilizer, as well as big economic gains from diversifyingproducts that came from making better use of waste. Using biodigester technology to turn biomass into energy is another way to cut down on greenhouse gas emissions from manure waste. These findings provide a strong basis for encouraging the implementation of improved coffee and dairy cow integration through a series of fiscal incentive policies and farmer assistance.